2021
DOI: 10.1111/bjh.17743
|View full text |Cite
|
Sign up to set email alerts
|

Serological SARS‐CoV‐2 antibody response, potential predictive markers and safety of BNT162b2 mRNA COVID‐19 vaccine in haematological and oncological patients

Abstract: Summary Haemato‐oncological patients are at risk in case of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) infection. Currently, vaccination is the best‐evaluated preventive strategy. In the present study, we aimed to assess serological response, predictive markers, and safety of BNT162b2 in haemato‐oncological patients. A total of 259 haemato‐oncological patients were vaccinated with two 30 µg doses of BNT162b2 administered 21 days apart. Serological response was assessed by ELECSYS® Anti‐SARS‐C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
43
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 20 publications
5
43
2
1
Order By: Relevance
“…Following title and abstract review, 1,233 records were excluded given that they reported non-original findings, did not include cancer patients, or did not assess COVID-19 vaccines’ immunogenicity. Of the 54 articles that underwent full-text review, 35 articles[ [17] , [18] , [19] , [20] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] were considered eligible and were included in the meta-analysis ( Figure 1 ).
Figure 1 The PRISMA flowchart summarizing the process for the identification of eligible studies.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following title and abstract review, 1,233 records were excluded given that they reported non-original findings, did not include cancer patients, or did not assess COVID-19 vaccines’ immunogenicity. Of the 54 articles that underwent full-text review, 35 articles[ [17] , [18] , [19] , [20] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] were considered eligible and were included in the meta-analysis ( Figure 1 ).
Figure 1 The PRISMA flowchart summarizing the process for the identification of eligible studies.
…”
Section: Resultsmentioning
confidence: 99%
“…of cancer patients No. of controls Patients’ age (years) Type of cancer Vaccine type Vaccine scheme Reported outcomes Addeo et al[ 17 ] Switzerland/USA Multicenter, prospective, cohort 244 NA 63 (IQR 55–69) Hematologic malignancy and solid tumor mRNA (BNT162b2/mRNA1273) Incomplete and complete Anti-S IgG Ab, adverse effects, SARS-CoV-2 infection Agha et al[ 41 ] USA Single-center, prospective, cohort 67 NA 71 (IQR 65-77) Hematologic malignancy mRNA (BNT162b2/mRNA1273) Complete Anti-S IgG Ab Barrière et al[ 42 ] France Single-center, prospective, cohort 122 29 69.5 (range 44-90) Solid tumor mRNA (BNT162b2) Incomplete and complete Anti-S IgG Ab, adverse effects Benda et al[ 37 ] Austria Single-center, prospective, cohort 259 NA 65.1 (SD 12.2) Hematologic malignancy and solid tumor mRNA (BNT162b2) Incomplete and complete Anti-S IgG Ab, adverse effects, SARS-CoV-2 infection Benjamini et al[ 53 ] Israel Multi-center, prospective, cohort 373 NA 70 (range 40-89) Hematologic malignancy mRNA (BNT162b2) Complete Anti-S IgG Ab, anti-N IgG Ab, adverse effects Bird et al[ 43 ] UK Single-center, retrospective, cohort 93 NA 67 (IQR 59-73) Hematologic malignancy mRNA (BNT162b2) and viral vector (AZD1222) Incomplete Anti-S IgG Ab Chowdhury et al[ …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a matter of the fact circulating anti-S antibodies were detected at very low levels (16.7 UI/ml). This case shows that accurate clinical history and lab tests addressing humoral immunity are mandatory in patients who received anti-SARS-CoV2 vaccine and were however infected [ 1 , 2 ].…”
mentioning
confidence: 99%